Nonarteritic anterior ischemic optic neuropathy: cause, effect, and management - Berry S; Lin WV; Sadaka A; Lee AG (Eye and Brain, 2017)
Shauna Berry,1 Weijie V Lin,2 Ama Sadaka,1 Andrew G Lee1–7 1Department of Ophthalmology, Blanton Eye Institute, Houston Methodist Hospital, Houston, TX, USA; 2Department of Ophthalmology, Baylor College of Medicine, Houston, TX, USA; 3Department of Ophthalmology and Visual Sciences, University of Texas Medical Branch (UTMB), Galveston, TX, USA; 4Department of Ophthalmology, 5Department of Neurology, 6Department of Neurosurgery, Weill Cornell Medicine, Houston, TX, USA; 7Department of Ophthalmology, The University of Texas MD Anderson Cancer Center, Houston, TX, USA Abstract: Nonarteritic anterior ischemic optic neuropathy (NAION) is the most common form of ischemic optic neuropathy and the second most common optic neuropathy. Patients are generally over the age of 50 years with vasculopathic risk factors (eg, diabetes mellitus, hypertension, and obstructive sleep apnea). The exact mechanism of NAION is not fully understood. In addition, several treatment options have been proposed. This article summarizes the current literature on the diagnosis, treatment, and management of NAION. Keywords: anterior ischemic optic neuropathy, nonarteritic anterior ischemic optic neuropathy, ischemic optic neuropathy